LEGAL PROTECTION POLICY FOR THE PEOPLE IN HANDLING COVID-19: A COMPARISON OF INDONESIA AND AUSTRALIA - Tinambunan, Hezron Sabar Rotua; Kusuma, Febrian Indar Surya; Permatasari, Vivi Ayudya; Sugiarto, Aditya Ferryan; Tajudin, Amalina Ahmad (Realism: Law Review, 2025)
In terms on handling COVID-19, the whole world is struggling to provide legal protection for its people, including Indonesia and Australia. Surely, Indonesia and Australia have made efforts to provide protection for their people in the form of legal provisions as a consequence of adhering to the rule of law. Thus, the purpose of this study is to examine how Indonesia and Australia issue policies for legal protection for the people in their efforts to deal with COVID-19. This article uses legal research in an effort to answer juridical problems. The results of the discussion show that Indonesia in its efforts to deal with COVID-19 issued a policy of budget refocusing, Large-Scale Social Restrictions to the Enforcement of Restrictions on Micro Community Activities. Meanwhile, Australia in an economic effort issued a COVID-19 grant program policy in Eligible States and Territories if it was appropriate and other efforts made by Australia in handling COVID-19, namely locking in areas where new cases identified. The research was conducted solely for the purpose of producing a substantive picture of the impact of COVID-19 so as to be able to produce policies that do not contradict the existing situation.